Hasil Pemilihan Presiden dan Pasar Saham: Studi Kasus Indonesia Tahun 2024 - Elva Farihah; Okta Sindhu Hartadinata (Universitas Budi Luhur, 2025)
The aim of this research is to test empirical evidence of presidential election result in 2024 and Indonesian stock market reaction. The sample object of this research is companies listed on Compass Index 100, Indonesian Stock Exchange (BEI). The research uses event study methodology. Based on purposive sampling criteria, the sample obtained resulted in 90 companies. Tests in this research show that there is an insignificant difference in average abnormal return before and after the result day. This research has the implication that market responses to political event. Therefore, political stability can affect market confidence and investor behaviour.